2021
DOI: 10.30865/mib.v5i4.3222
|View full text |Cite
|
Sign up to set email alerts
|

Klasifikasi Physical Activity Berbasis Sensor Accelorometer, Gyroscope, dan Gravity menggunakan Algoritma Multi-class Ensemble GradientBoost

Abstract: The current generation of smartphones is increasingly sophisticated, equipped with several sensors such as accelerometer, gravity sensor, and gyroscope that can be used to recognize human activities such as going up stairs, going down stairs, running and walking. To get information, the data will be grouped using statistical methods. The performance of statistical methods has shortcomings in classifying data because of the procedures that must be met. To cover this shortcoming, the ensemble technique is used. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
1
0
1
Order By: Relevance
“…The results of this research indicate that machine learning algorithms, including both the decision tree and support vector machine, can effectively predict physical activity behavior among adolescents. This finding aligns with previous research, which has shown that machine learning methods perform exceptionally well in studying physical activity (Aziz et al, 2021). Several earlier studies that predicted physical activity using machine learning, specifically the support vector machine model (Cheng et al, 2021;Chong et al, 2021;Vanstrum et al, 2023;Wang, 2022;Zhou et al, 2019), also reported that the support vector machine model demonstrates high accuracy in predicting physical activity.…”
Section: Discussionsupporting
confidence: 90%
“…The results of this research indicate that machine learning algorithms, including both the decision tree and support vector machine, can effectively predict physical activity behavior among adolescents. This finding aligns with previous research, which has shown that machine learning methods perform exceptionally well in studying physical activity (Aziz et al, 2021). Several earlier studies that predicted physical activity using machine learning, specifically the support vector machine model (Cheng et al, 2021;Chong et al, 2021;Vanstrum et al, 2023;Wang, 2022;Zhou et al, 2019), also reported that the support vector machine model demonstrates high accuracy in predicting physical activity.…”
Section: Discussionsupporting
confidence: 90%
“…However, this research is merely limited to two classes. Research [15]- [17] proposed a classification of human physical activity using accelerometer sensors, gyroscopes, and gravity sensors. The ensemble technique was employed by combining logistic regression as initial classification and gradient boost to correct misclassified logistic regression [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…Berdasarkan hasil yang diperoleh, ensemble SVM dengan Stacking memberikan peningkatan kinerja ± 1%. Penelitian [19], [20] menggunakan…”
unclassified